HANDBOOK OF BIOLOGICAL CONFOCAL MICROSCOPY - Pawley, James B. (Springer, 2006)
Once the second edition was safely off to the printer, the 110 authors breathed a sigh of relief and relaxed, secure in the belief that they would “never have to do that again.” That lasted for 10 years. When we ﬁnally awoke, it seemed that a lot had happened. In particular, people were trying to use the Handbook as a textbook even though it lacked the practical chapters needed. There had been tremendous progress in lasers and ﬁber-optics and in our understanding of the mechanisms underlying photobleaching and phototoxicity. It was time for a new book. I contacted “the usual suspects” and almost all agreed as long as the deadline was still a year away. That was in 2002. Three years later, most of the old chapters have been substantially or totally rewritten. Although 12 of the chapters are on topics that have either been rendered obsolete by improvements in instrumentation or changes in research interest have been dropped, some have been replaced by chapters on similar topics. To make the Handbook of more use as a textbook, we have added an extended appendix about practical multiphoton imaging and another describing the operation of CCD cameras in some detail. There is a new series of practical chapters on confocal microscopy and the selection of dyes, as well as on ion imaging, and on methods for studying brain slices, embryos, bioﬁlms and plants (two). There is also a new chapter describing in some detail how such components as interference ﬁlters, acousto-optical devices, and galvanometers are made and what parameters limit their performance. The single chapter on 3D image analysis now has the company of two more on automated 3D image analysis and a third on high-content screening and a fourth on database management. Chapters have been added describing techniques that have only recently come to the fore, such as patterned-illumination ﬂuorescence microscopy, ﬂuorescence resonance energy transfer (FRET) and the generation and detection of second- and third-harmonic signals. In addition, new imaging techniques such as stimulated emission depletion (STED), coherent anti-Stokes Raman (CARS) imaging and selected plane illumination (SPIM) now have their own chapters and there are also chapters that connect the world of 3D light microscopy to the larger world of micro-CT and micro-MRI and the smaller world revealed by the scanning and transmission electron microscopes. To round out the story we even have a chapter on what PowerPoint does to the results, and the annotated bibliography has been updated and extended.
Keywords: MICROSCOPY